Pengaruh Disimplin Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Dinas Pendidikan Dan Kebudayaan Kabupaten Serang - Marsah Auliah; Sofiatul Fitri; Repliyana; Fatihah (Jurnal Cakrawala Akademika, 2025)
This study aims to determine how much influence work discipline and leadership style have on the performance of employees of the Serang Regency Education and Culture Office. The research variables are work discipline (X1), leadership style (X2), employee performance (Y). This research method uses a quantitative method with a causal research design (cause and effect). The population in this study amounted to 46 people with a sample of 30 employees, the sampling technique used a probability sampling technique using a random sampling sample. Data collection was carried out through a questionnaire that had been tested for validity and reliability, while data analysis was carried out using the multiple regression method. The results of the study indicate that work discipline has a positive and significant effect on employee performance, even when there is a combination of poor leadership styles. Work discipline has also been shown to provide a positive and significant contribution to employee performance, even though it is applied simultaneously with a negative leadership style.